Medkulturni dialog v šolski knjižnici - Hanuš, Barbara (Knjižnica, 2009)
Nowadays many countries are confronted with the sudden and increased number of child immigrants which has a strong impact on education systems. A school library plays an important role in the development of intercultural dialogue as it keeps materials in many languages and develops different waysof youth activity. Fiction and non fiction show the abundance of habits and cultures inthe world, they reveal different life stories and encourage the idea of diversity. A youth library encourages the intergenerational and intercultural dialogue. In the environment with a lot of immigrants it is very important for the library to consider the needs of the youth and to cooperate with their parents, too. The school in which most of the pupils do not speak Slovenian as their mother tongue is described. Library activities encourage their interest in learning the language of their new environment. Well developed literacy has a great impact on their educational results, but it is true that people can not understand other cultures unless they are aware of their own cultural identity.
Keywords: medkulturni dialog; migranti; pismenost; literacy; branje; bralna motivacija; komunikacija; šolske knjižnice